Food sovereignty and popular feminism in Brazil - Campos Motta, Renata; Teixeira, Marco Antonio (Anthropology of food, 2022)
The Marcha das Margaridas is a coalition of women and feminism movements, agrarian movements, trade unions, and international organizations that emerged in 2000. Women’s organizations that are part of a rural trade federation lead the process. While its initial agenda included gendered class-based demands for the recognition of women’s work in food production, access to land titles and labour rights, the Marcha das Margaridas progressively incorporated other topics, such as agroecology and food sovereignty. The article addresses three questions: How did food sovereignty enter their agenda? What is the meaning of food sovereignty for them? How can food sovereignty be understood from a (popular) feminist perspective? Our research is based on participant observation in the last two Marchas (2015 and 2019), interviews with activists, and document analysis.
Gesehen am 05.04.2023